2014
DOI: 10.4274/tjo.72692
|View full text |Cite
|
Sign up to set email alerts
|

Kartal Eğitim ve Araştırma Hastanesi Kornea Bankası Donörlerine Ait Speküler Mikroskopi Verileri

Abstract: Amaç: Göz bankasında speküler mikroskopinin (SM) gerekliliği açısından donör kornea endotel hücre morfolojisinin donörün epidemiyolojik özellikleri ve ölüm zamanı ile ilişkisini değerlendirmek. Gereç ve Yöntem: Dr. Lütfi Kırdar Kartal Eğitim ve Araştırma Hastanesi'ne bağlı Kornea Bankası'nda 2010-2012 tarihleri arasında alınan donör kornealara ait speküler mikroskopi (SM) verileri retrospektif olarak değerlendirildi. Bulgular: Yaş ortalaması 40,11±15,51 yıl olan 606 donörden 1180 adet kornea dokusu alınmıştı v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
(24 reference statements)
0
4
1
Order By: Relevance
“…Some studies investigated gender-based differences in endothelial cell morphology, some of them reporting ECC differences between both genders, but some others not [24,25]. Kartal et al [21] reported that female donors had a greater MCA, while a study from India, reported higher CV in female donors [26]. Our results did not reveal any significant difference between both sexes.…”
Section: Discussioncontrasting
confidence: 51%
See 3 more Smart Citations
“…Some studies investigated gender-based differences in endothelial cell morphology, some of them reporting ECC differences between both genders, but some others not [24,25]. Kartal et al [21] reported that female donors had a greater MCA, while a study from India, reported higher CV in female donors [26]. Our results did not reveal any significant difference between both sexes.…”
Section: Discussioncontrasting
confidence: 51%
“…As a general rule, it is recommended that corneal harvesting should be completed within 12 hours [28], although there is still no consensus regarding the upper limit of this time, and it may well be prolonged in some cases [29]. Kartal et al [21] showed that ECC was greatest in the ≤3 hours group, although the difference was statistically non-significant. Our study showed a significant negative correlation between time from death to cornea harvesting and cell count, 6A.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Parekh et al 25 found that CECD in the central cornea decreased by 0.59% per year, in the paracentral by 0.45% per year, and in the periphery by 0.40% per year (mean, 0.5%–0.6%) because of aging in healthy individuals. In the postmortem period, the highest CECD was detected ≤3 hours 30 . Postmortem interval is not thought to affect endothelial cell viability up to 32 hours postmortem, 31,32 but a longer PMI causes a decrease in endothelial cells 33 …”
Section: Discussionmentioning
confidence: 93%